2018
DOI: 10.1111/nin.12230
|View full text |Cite
|
Sign up to set email alerts
|

Ways of knowing on the Internet: A qualitative review of cancer websites from a critical nursing perspective

Abstract: People diagnosed with cancer typically want information from their doctor or nurse. However, many individuals now turn to the Internet to tackle unmet information needs and to complement healthcare professional information. The purpose of this study was to qualitatively explore the content of commonly searched cancer websites from a critical nursing perspective, as this information is accessible, and allows patients to address their information needs in ways that healthcare professionals cannot. This qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Overall, only very limited evidence, with a lack of methodological consistency, is available with regard to the use and impact of the Internet on people with BCa. With the Internet and online social spaces now an important source of health information, clinicians face the challenge of understanding how Internet information impacts on patients’ decision‐making and whether patients have the ability to appraise it critically . There is evidence of a mismatch between the visibility and the quality of most of the cancer information websites, leading to false information and suboptimal decisions .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, only very limited evidence, with a lack of methodological consistency, is available with regard to the use and impact of the Internet on people with BCa. With the Internet and online social spaces now an important source of health information, clinicians face the challenge of understanding how Internet information impacts on patients’ decision‐making and whether patients have the ability to appraise it critically . There is evidence of a mismatch between the visibility and the quality of most of the cancer information websites, leading to false information and suboptimal decisions .…”
Section: Discussionmentioning
confidence: 99%
“…The paternalist approach in the Norwegian online cancer information is not in line with the recent cancer strategy in Norway, 23 in which patients participate more and influence their treatment. However, Haase et al 42 found that the dominant discourse in online patient information focuses on treatment, prognosis, and cure, with a lack of sociopolitical, ethical, and personal information. Technology-mediated platforms might lead to static attention and less social feedback in patients' interpretation and handling of information by health care professionals.…”
Section: Advances In Nursing Science/july-september 2023mentioning
confidence: 99%
“…Evaluation or critical appraisal is what bridges finding information and using that information in clinical practice (Carter‐Templeton, 2013). Practicing nurses need the skills to determine what is good information, not only for clinical application but also to help patients who increasingly turn to the Internet for information to learn about their health conditions (Cader, 2013; Gilmour et al, 2012; Shiferaw et al, 2020), even though that information is not as holistic as what nurses can provide (Haase et al, 2018). Yet, Miller et al (2010) established in the abstract of their study that “nurses are challenged to find and use reliable, credible information to support clinical decision‐making and to meet expectations for evidence‐based nursing practice.” This finding was echoed by Carter‐Templeton (2013) who found that the critical appraisal process is not well understood and that nurses mainly rely on other nurses for information.…”
Section: Introductionmentioning
confidence: 99%